NURSES’ KNOWLEDGE TOWARD MANAGEMENT OF POSTOPERATIVE PAIN - AL-Hadrawy , Zainab Abidzaid Abid; Alnassar, Hawra'a Ghannam; Mohammed Baqer Hasan; Ali Takleef Noor Algburi (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: Study aims to assess nurses' knowledge toward pain management post operatively and to find out the relationship between nurses' knowledge and their demographic data. Method: A descriptive cross-sectional study design was conducted at Al-Najaf city in the southern region of Iraq in Al-Zahra'a Teaching Hospital from January 28, 2025, to 6th April, 2025, in order to assess the nurses’ knowledge regarding post-operative pain management. The methodological strategies for data collection used an assessment questionnaire survey methodology. Results: In the present study, an assessment of nurses' knowledge concerning post-operative pain management revealed a good level of understanding. Furthermore, there is a significant relationship between nurses' knowledge regarding management of post-operative pain and their level of education and training courses. Novelty: Despite advancements in pain management, many patients still suffer due to a lack of nurses’ knowledge or negative attitudes toward handling.